Vulvar Skin Disorders throughout Lifetime: About Some Representative Dermatoses. (8th January 2014) - Doyen, Jean; Demoulin, Stéphanie; Delbecque, Katty; Goffin, Frédéric; Kridelka, Frédéric; Delvenne, Philippe
Abstract : The objective of this paper is to present general considerations which should be kept in mind by clinicians in charge of women with vulvar diseases. Four representative vulvar dermatoses are described. Lichen simplex chronicus is a pathological condition related to chemical and mechanical irritant agents. Detrimental effects of these irritants, in the presence of other dermatoses, have to be considered when therapeutic responses are unsatisfactory. Lichen sclerosus is the most common vulvar dermatosis in elderly. However, it should be kept in mind that it may be diagnosed at any age. Lichen planus, in spite of sharing a similar range of etiological factors with lichen sclerosus, is a very distinct entity. Finally, Paget's disease, although rare, is also described especially because of the challenge it represents both clinically and therapeutically.